2017
DOI: 10.18488/journal.8/2017.5.1/8.1.23.34
|View full text |Cite
|
Sign up to set email alerts
|

Audit in Russian Federation and the Research Toward the Determination of the Functioning of Audit Mechanism

Abstract: Although the development of audit laws in Russia corresponds Contribution/ OriginalityIn the scope of this study, using statistical data of the Russian Ministry of Finance, main indicators pertaining to the audit of the 2013-2014 year are included. As a result of examination of the information for every two years, both positive and negative developments in the audit field have been revealed. In this context, this study, including legal developments in Russia and comparative data, will add value to the relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This research employs static estimators Panel OLS which have also been used in previous research (Calomiris and Wilson, 2004;Laeven and Levine, 2009;Demirgüç-Kunt and Huizinga, 2010;Akgun and Tektufekci, 2017). This method allows the research to control for heterogeneity, because each bank in the sample has different credit policy and different approach to risk taking and managing the risk.…”
Section: Methodsmentioning
confidence: 99%
“…This research employs static estimators Panel OLS which have also been used in previous research (Calomiris and Wilson, 2004;Laeven and Levine, 2009;Demirgüç-Kunt and Huizinga, 2010;Akgun and Tektufekci, 2017). This method allows the research to control for heterogeneity, because each bank in the sample has different credit policy and different approach to risk taking and managing the risk.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was also concurred that talents" knowledge, skills and abilities can be developed through the behavioral modification tasks such as technical training and coaching (Brooks andNafukho, 2006, Ab Rashid, Supian &Bojei 2018). Another study also found that talents" mindset assisted organization in recruiting the best talents for their organization by building a talent management strategy based on competency profiling (Bhatnagar, 2009, Akgun & Tektufekci 2017.…”
Section: Talent Management Of Muslim Professionals In Ifimentioning
confidence: 84%
“…Thus, a deeper understanding of this "commercialization journey" by means of the case study approach would help in providing context for the factors that contribute to successful R&D commercialization as found in many of the empirical research conducted on this topic to date (for discussion on case study research design and methods, refer to Akgun and Tektufekci, 2017;Natsheh et al, 2015;Akhir et al, 2018;OECD, 2013;Aldulaimi and Abdeldayem, 2018 demonstrates how a portfolio of case study research designs fits differently to a theory continuumtheory understanding, theory-building, theory development, and theory testing; for recent examples of the use of case study research on technology R&D commercialization, refer to Ale, 2018; Booz Allen Hamilton, 2012; Pellikka and Malinen, 2014).…”
Section: Methodsmentioning
confidence: 99%